Exploring the Relationship Between Chinese EFL Students' Grit, Well-Being, and Classroom Enjoyment - Yang, Peng (Frontiers in Psychology, 2021)
It has been documented that grit plays an indispensable role in the process of language learning and teaching. It is postulated that gritty people are more about to involve in classroom practice and be motivated even in the light of challenges; however, what remains vague is the interplay of grit, well-being, and classroom enjoyment. To this end, 335 male and female Chinese EFL learners who were studying English in 28 universities took part in this study. They completed the three questionnaires including, the grit scale questionnaire (Grit-S), foreign language enjoyment scale, and PERMA well-being scale. Pearson coefficient of correlation was run to investigate the first research question of the study while after checking the preliminary assumptions, for the second research question, a multiple regression analysis was used. The findings of the study demonstrated that there is a positive relationship between learners’ grit and enjoyment, and high degrees of enjoyment were interrelated to high degrees of grit. The findings of the study also signified that grit significantly predicted students’ well-being and also it is the predictor of classroom enjoyment. Finally, some implications and recommendations have been offered for language teaching stakeholders in educational settings.